Current status of various coolant applications in machining of nickel-base superalloys. (2023) - Soumikh Roy; Kumar, Ramanuj; Satpathy, Ashutosh; Kumar Sahoo, Ashok
Abstract: Nickel-chromium super-alloys are preferred over steel as they provide excellent performance over a broad temperature range of cryogenic temperature to 1400 Fahrenheit. These alloys possess both high impact and tensile strength, thus it is one of the most desirable raw material for aeronautical and marine industries. Apart from all these advantages, they are very hard to machine and a huge magnitude of heat arises during machining operations which directly affects the product quality and surface texture of the finished products. To overcome all these problems, many researchers have implemented different types of coolants to minimize temperature generation, surface roughness, and tool wear. Coolants also harm both human health and the ecosystem if it is not handled properly and their disposal remains a challenge to our civilization. To overcome these challenges most industries preferred biodegradable vegetable oil base coolants over conventional mineral oil coolants. Researchers are continuously working on different methods to intensify the thermal conductivity and heat-dissipating capability of the coolants. This gave birth to a new era of coolants, where nanoparticles are mixed in a base oil to intensify their lubricating and cooling properties. These types of coolants are known as nanofluids which are colloidal mixtures made by the combination of nanoparticles and a base fluid. Nanofluids are now renowned in the entire world because of their high thermal conductivity, lubrication, and heat dissipation abilities. These papers provides a concise review of the effects of the several cutting fluids such as synthetic oil, mineral oil, vegetable oil, and nanoparticle-based cutting fluid on various machining outputs such as surface roughness and wear on tool interface while machining of the nickel-based alloy under an MQL environment. A concise review of different nanofluid preparation techniques is also included in this paper to acquire close knowledge about the manufacturing of different nanofluids.